2021
DOI: 10.1155/2021/5571144
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Chest X‐Ray Severity in COVID‐19 and Age in Mexican‐Mestizo Patients: An Observational Cross‐Sectional Study

Abstract: Introduction. Chest X-ray (CXR) is used for the initial triage of patients with suspected COVID-19. Studies of CXR scoring in the European population found a higher score in males than in females and significantly correlated with age. Because there have not been studies in the Mexican-mestizo community, we aimed to compare the differences in CXR scores between males and females and their correlation with age after controlling comorbidities like diabetes and hypertension. Materials and Methods. A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The results are summarized in Table 7. For the whole dataset, there was almost no correlation with age, Rs = −0.004, p-value = 0.884; in [35], a low positive correlation was obtained, but it was not statistically significant. Grouped by gender, the correlation result was low and positive in both cases, but not significant, Rs = 0.167 p-value < 5.52 × 10 −10 for the female group, and Rs = 0.065 p-value < 5.13 × 10 −4 for the male one, confirming the results in [35].…”
Section: Covid-19 Risk Indicator Statistical Analysismentioning
confidence: 80%
See 2 more Smart Citations
“…The results are summarized in Table 7. For the whole dataset, there was almost no correlation with age, Rs = −0.004, p-value = 0.884; in [35], a low positive correlation was obtained, but it was not statistically significant. Grouped by gender, the correlation result was low and positive in both cases, but not significant, Rs = 0.167 p-value < 5.52 × 10 −10 for the female group, and Rs = 0.065 p-value < 5.13 × 10 −4 for the male one, confirming the results in [35].…”
Section: Covid-19 Risk Indicator Statistical Analysismentioning
confidence: 80%
“…For the whole dataset, there was almost no correlation with age, Rs = −0.004, p-value = 0.884; in [35], a low positive correlation was obtained, but it was not statistically significant. Grouped by gender, the correlation result was low and positive in both cases, but not significant, Rs = 0.167 p-value < 5.52 × 10 −10 for the female group, and Rs = 0.065 p-value < 5.13 × 10 −4 for the male one, confirming the results in [35]. We divided the cases by age groups, and, for each age group, we studied the score distribution testing the differences between genders with the Mann-Whitney U test (alpha = 0.05).…”
Section: Covid-19 Risk Indicator Statistical Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…Other authors as Albrandt-Salmeron et al 91 agree that there is a correlation between age and some symptoms and image findings, but they find out that upon the Mexican-mestizo community, there are no significant different in terms of patient sex 91 , meanwhile Borghesi and Maroldi, 2020 refutes this idea in a study over Italy that finds significantly higher pulmonary insolvents in males than in females 92 , this information can be interpreted in different ways first Mexican study use patients of only one hospital, but they have 1000 chest x-ray images, and Italian study use information of 100 hospitals without specifying the number of images, and both are using the CXR scoring system for COVID-19 pneumonia, proposed by Borghesi and Maroldi of the Italian study 92 that is also used On BrixIA dataset for the severity label, the information shows two main possibilities as an overview, first using 100 hospitals shows more generalization on the population than only using one, meaning there is a tendency on pulmonary involvement’s grater in males rather than females, but also we can argue that both studies are equally valid, but the differences between the results depends on the population that the study focus on meaning that on Italian or even European population the COVID-19 findings are more usual in males while in Mexico there is not a marked difference.…”
Section: Discussionmentioning
confidence: 96%
“…There is evidence showing that a higher CT severity score was significantly correlated with male gender, older age groups, and a likely positive PCR test ( 12 ). A recent prospective study ( 80 ) has also found that the severity of COVID-19 was associated with higher age, male sex, and higher BMI. The CCT severity score index of lung involvement in the acute phase was also associated with restriction and a reduction in diffusion capacity in follow-up.…”
Section: Comparative Analysismentioning
confidence: 91%